Quantifying bioenergy potential and environmental impacts of agricultural residues; a Comparative analysis with global benchmarks - Amir Azizpanah; Morteza Taki (PLoS ONE, 2025)
Finding sustainable solutions for biofuel production from agricultural waste is crucial for reducing pollution and enhancing waste management. Agricultural residues—including crop waste, livestock manure and other organic materials—can be effectively converted into biofuels. Given the substantial volume of agricultural residues and their inadequate management in Iran, evaluating the potential for bioenergy production and determining the distribution of this renewable resource, is essential. This study assessed the bioenergy production potential from agricultural residues in Khuzestan Province, Iran. Data were collected from library resources and crop statistics for the agricultural year 2023–2024. The results indicated that the annual production of field and horticultural crops totaled 13,907,333.42 tons. The Theoretical Biomass Potential (TBP), Theoretical Energy Potential (TEP) and Available Energy Potential (AEP) were calculated as 5,496,297 tons, 92,283,088 GJ and 14,582,753 GJ, respectively. The potential electrical energy and power output from the total residues of the studied crops in a Combined Heat and Power (CHP) system were estimated at 1,364,122 MWh and 194.8745769 MWh, respectively. Additionally, the thermal energy potential was found to be 1,562,555.5 MWh, with a power capacity of 223.22 MWh. Environmental analysis indicated that the Global Warming Potential (GWP) was estimated at 774,334.45 tons of CO₂-equivalent.